1993
DOI: 10.1136/bjo.77.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study on premature infants with and without retinopathy of prematurity.

Abstract: The ocular complications in population of 131 premature infants, with and without retinopathy of prematurity (ROP) are reported. An increased incidence of strabismus (20% with ROP and 25% without ROP) and myopia (27-5% with ROP and 8-8% without ROP) was shown. Significant visual loss occurred in 10-7% overall, increasing to 35% with stage 3 disease and 100% with stage 4. With the increased survival rate of premature infants, the relevance to future management of this expanding group of young people is consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
3
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 21 publications
5
41
3
9
Order By: Relevance
“…In an effort to explain this they proposed that ROP may interfere with the normal reduction in lens power that occurs after birth? 6 We also found that PSL was increased in the stage 3 group. Therefore we can deduce that it is anterior segment arrest causing anterior displacement of the crystalline lens, together with increased LT and PSL, that were causative factors in the development of myopia in this cohort.…”
Section: Discussionsupporting
confidence: 60%
“…In an effort to explain this they proposed that ROP may interfere with the normal reduction in lens power that occurs after birth? 6 We also found that PSL was increased in the stage 3 group. Therefore we can deduce that it is anterior segment arrest causing anterior displacement of the crystalline lens, together with increased LT and PSL, that were causative factors in the development of myopia in this cohort.…”
Section: Discussionsupporting
confidence: 60%
“…Muitos autores, no início deste estudo, já defendiam que o peso ao nascimento deveria ser abaixo de 1.500 g e idade gestacional menor que 32 semanas (1,5,(9)(10)23,(25)(26)(27) . Neste estudo foi determinada idade gestacional menor ou igual a 36 semanas e peso ao nascer menor ou igual a 1.600 g. Os prematuros com idade gestacional de 36 semanas e 3 dias, era arredondada para 36 semanas.…”
Section: Discussionunclassified
“…[1][2][3][4] There have been reports that cryotherapy in threshold ROP contributes to the development of myopia and that laser photocoagulation, in comparison, produces less myopic shift. [5][6][7] However, Quinn et al felt that the cryotherapy did not result in additional myopia but that the high myopia was related to the cicatricial retinopathy or severity of ROP.…”
mentioning
confidence: 99%